2018
DOI: 10.1002/jcb.26886
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Efficacy of different drugs in the treatment of minimal hepatic encephalopathy: A network meta‐analysis involving 826 patients based on 10 randomized controlled trials

Abstract: Minimal hepatic encephalopathy (MHE), a complex neuropsychological complication of cirrhosis, is characterized by delayed reaction time and the inhibition of abnormal response. This network meta-analysis (NMA) was adopted to compare the efficacy of five drugs including lactulose, probiotics, rifaximin, acetyl-L-carnitine (ALC), and L-Ornithine L-aspartate (LOLA) in the treatment of MHE. The Cochrane Library, PubMed, and Embase databases were searched for any existing entail on these five drugs from the incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The most common commercialized probiotics are lactose-fermenting Lactobacilli and Bifidobacteria . A meta-analysis made by Cai et al [49], involving 826 minimal HE patients, indicated that probiotics had better efficacy in decreasing ammonia serum levels, endotoxemia levels, and hospitalization rates. Dhiman et al [50] enrolled 130 cirrhosis patients including 21 HBV- or HCV-derived cirrhosis, and either probiotic VSL#3 or a placebo is given for 6 months.…”
Section: Clinical Implications Of Gut Microbiotamentioning
confidence: 99%
“…The most common commercialized probiotics are lactose-fermenting Lactobacilli and Bifidobacteria . A meta-analysis made by Cai et al [49], involving 826 minimal HE patients, indicated that probiotics had better efficacy in decreasing ammonia serum levels, endotoxemia levels, and hospitalization rates. Dhiman et al [50] enrolled 130 cirrhosis patients including 21 HBV- or HCV-derived cirrhosis, and either probiotic VSL#3 or a placebo is given for 6 months.…”
Section: Clinical Implications Of Gut Microbiotamentioning
confidence: 99%
“…To date, 10 meta-analyses including seven systematic reviews (Jiang et al, 2008;Eltawil et al, 2012;Hu and Tang, 2013;Wu et al, 2013;Kimer et al, 2014;Wang, 2015;Zhuo et al, 2019) and three network meta-analyses (Zhu et al, 2015;Cai et al, 2018;Dhiman et al, 2020), have been published on efficacy or safety of rifaximin for HE treatment. Most of these meta-analyses focused on one control arm or one type of HE, and their results seem equivocal and inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Although various drugs have been given for patients with MHE [ 40 44 ] to decrease ammonia levels or improve mental status, drugs that are effective against MHE are unclear. We showed that the concentration of BCAA correlated with the presence of MHE, suggesting that administration of BCAA may be a reasonable treatment for MHE, because of its potential efficacy ameliorating skeletal muscle mass loss.…”
Section: Discussionmentioning
confidence: 99%